Where we started [compact disc] - Rhett, Thomas, 1990- (Valory Music Co./Big Machine Label Group, 2022)
Thomas Rhett returns with a mix of uptempo, transcendent romance and sonic trailblazing songs as country's resident good-life philosopher.